2019
DOI: 10.1111/vsu.13250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative antibiotics on rates of infection and implant removal after tibial tuberosity advancement in 1,768 canine stifles

Abstract: Objective To report infection rate, implant removal rate, and postoperative antibiotic therapy after tibial tuberosity advancement (TTA) in dogs. Study design Retrospective study. Animals One thousand seven hundred sixty‐eight stifles in 1,732 dogs. Methods Medical records (January 2007‐December 2011) of dogs treated with a TTA were reviewed. Cases were included if at least 1 year of postoperative follow‐up was available and no additional procedures were performed on the stifle. Date of surgery, date of cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have been conducted to determine implant removal rate for surgeries such as tibial tuberosity advancement and tibial plateau levelling osteotomy; however, these studies focus on implant infection and perioperative antibiotic medication use, as implant migration is uncommon with these procedures. 11 12 In this study, although animals that received postoperative antibiotic medications were at a higher risk of requiring non-elective explant, infection was not recorded in any of the cases. It may be that whatever caused a surgeon to decide on using antibiotic medications may have contributed to the need for non-elective explant.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have been conducted to determine implant removal rate for surgeries such as tibial tuberosity advancement and tibial plateau levelling osteotomy; however, these studies focus on implant infection and perioperative antibiotic medication use, as implant migration is uncommon with these procedures. 11 12 In this study, although animals that received postoperative antibiotic medications were at a higher risk of requiring non-elective explant, infection was not recorded in any of the cases. It may be that whatever caused a surgeon to decide on using antibiotic medications may have contributed to the need for non-elective explant.…”
Section: Discussionmentioning
confidence: 62%
“…Study group sizes varied between five subjects per group ( 56 , 58 ) and 1,732 subjects per group. The highest total number of subjects in one study was 1,732 dogs with 1,768 surgeries ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Infection rates of 2.3 to 33 per cent have been reported following TPLO, with 37.5 to 57.1 per cent of cases requiring implant removal for resolution (Brown and others 2016, Hans and others 2017, Cappelle and Barnhart 2019, Giannetto and Aktay 2019). Infection rates following TTA have been reported in 4.6 per cent to 15.4 per cent of cases, with between 1.3 per cent and 39 per cent of cases requiring implant removal for resolution (although the cage was not removed in the majority of cases) (Yap and others 2015, Hans and others 2017, Ferrell and others 2019). Similar infection rates of up to 14.5 per cent for CTCWO and 17.3 per cent for ECS have been reported, with the suture requiring removal in 53 per cent cases for resolution (Campbell and others 2016, Cox and others 2020).…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Factors associated with significantly increased infection rates include increased bodyweight, being a GSD, undergoing meniscectomy, surgeon experience (<20 procedures), increased surgical and anaesthesia time, and induction with propofol (Fitzpatrick and Solano 2010, Yap and others 2015, Lopez and others 2018, Giannetto and Aktay 2019, Cox and others 2020). Although some authors reported a significantly reduced risk of infection and/or major complications when antibiotics were given postoperatively (Fitzpatrick and Solano 2010, Hans and others 2017), others reported no benefit (Yap and others 2015, Campbell and others 2016, Lopez and others 2018, Ferrell and others 2019, Cox and others 2020).…”
Section: Postoperative Complicationsmentioning
confidence: 99%